Sensorial descriptors for vegetarian pigeon pea hamburger patties according to a focus group - Mora Peraza, Eliana Gabriela (2015)
The Pigeon Pea is a legume that has become an alternative food security crop, associated with improvement of the soil, fodder, green manure and the protection of hidric basins. It is rich in vitamins and proteins and considered nutritious for animals and humans. Four pilot plant tests with Costa Rican beans were done to produce an acceptable formulation of the hamburger patty. We preliminarily found that 15% of texturized soy, less than 1% of salt and 2% of Binder 2.0 were enough to create an acceptable patty for the consumer. Afterwards, a focus group of 12 people found that: a) the product belongs in four trends: good taste, ecology friendly, convenient and multipurpose; b) the target market can be children as well as adults or people with special needs (cholesterol, high blood pressure, diabetes); c) the senso rial descriptors were: healthy, non artificial flavors, with non transgenic soy, with spices (like garlic, onion, basil and rosemary), biodegradable packaging material, transparent lid, and red and yellow or green and orange packaging material; d) can be sold in macrobiotics shops, supermarkets, restaurants and school cafeterias; e) presentation can be 4 to 12 units with flavors like asparagus, mixed vegetables, palmetto and spinach. All participants reported good flavor, intermediate texture (rejected by most), and good color and appearance (cooked and frozen). With additional study, the product can be sold commercially.